The Royal Marsden Manual of Clinical Nursing Procedures - Dougherty, Lisa.; Lister, Sara E.; West-Oram, Alex. (Chichester, West Sussex ; Hoboken, NJ : John Wiley & Sons Inc., 2015)
The Royal Marsden Manual of Clinical Nursing Procedures has been the number one choice for nurses since it first published, over 30 years ago. One of the world's most popular books on clinical skills and procedures, it provides detailed procedure guidelines based on the latest research findings and expert clinical advice, enabling nurses and students to deliver clinically effective patient-focused care. The ninth edition of this essential, definitive guide, written especially for pre-registration nursing students, now includes a range of new learning features throughout each chapter that ha.
""Communicating with those who are worried or distressed""""Definition""; ""Related theory""; ""Evidence-based approaches""; ""Pre-procedural considerations""; ""Informing patients""; ""Related theory""; ""Evidence-based approaches""; ""Principles of giving information to a patient""; ""Pre-procedural considerations""; ""Communicating with those with specific psychological needs""; ""Denial and collusion""; ""Definitions""; ""Related theory""; ""Evidence-based approaches""; ""Anxiety""; ""Definition""; ""Anatomy and physiology""; ""Related theory""; ""Evidence-based approaches""
Includes bibliographical references and index.
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Print version record and CIP data provided by publisher.
WorldCat record variable field(s) change: 650
Keywords: Nursing -- Technique -- Handbooks, manuals, etc; Nursing; Nursing Process; Nursing Theory; Nursing Care -- methods; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Electronic books; Electronic books